SISTEM PENJADWALAN KULIAH DENGAN MENGGUNAKAN ALGORITMA GENETIKA - Simamora, Purwanto; ., Tulus; Batubara, Fakhruddin R (JURNAL PENELITIAN SAINTIKA, 2013)
Course scheduling is process of placing courses into availabletime-and classroom slots. As number of course activities andrequirement needed increase, the solution to scheduling problembecome more complicated. In order to get a good course scheduling,there are some important components such as lecturer, subject, student,curriculum, classroom and time. The limitation of rooms and time isoften become a problem in making the course scheduling. The additionnumber of the students and the subjects due to the application of thenew curriculum, and the other activity in university give the effects theusing of times and rooms. Course scheduling systems which isadaptable in every. changing that happened. The course schedulingmust be able to overcome the limitation of each component such as thenumber of the lecturer, times and rooms. This research uses twomethods in making the course scheduling which are by using thescheduling algorithm and without using the scheduling algorithm.These two methods will be combined into the genetic algorithm inorder to get a course scheduling which can reduce the problem in theavailability of rooms and times. The research result shows withoutusing the schedule algorithm these are 2 faults appear in the timeschedule and the minimum number of room which used is 9 rooms andconverged in the 1271h generation. But, by using the schedule algorithmthe number of the fault is no longer appear, the using of the roombecomes 8 rooms and converget in the 851h generation. It is concludedthat making the course scheduling by combining the schedulealgorithm and genetic algorithm is a right method in reducing the time fault and minimizing the using of the room.